Social Media Marketing and Electronic Word of Mouth at Coffee Shop: The Mediating Role of Brand Image on Purchasing Decisions - M Samsul Hidayat; Rayhan Abi Ramadhan; Aang Curatman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The aim of this study is to examine the impact of social media marketing (SMM) and electronic word of mouth (e-WOM) on purchasing decisions for Baraja Coffee Indonesia, with brand image serving as a mediating variable. The type of research used is associative research with a quantitative approach and data were collected by using questionnaires through Google Forms to consumers of Baraja Coffee Indonesia. A total of 210 respondents were selected using the accidental sampling method, based on who was available at Baraja Coffee Indonesia during the study. Data analysis was performed through Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS program. The findings of this study indicate that social media marketing and electronic word of mouth have a positive and significant influence on brand image. In addition, social media marketing shows a positive and significant influence on purchasing decisions, while electronic word of mouth has no effect on purchasing decisions. Furthermore, brand image is proven to have a positive and significant influence on purchasing decisions. Other findings show that brand image acts as a mediating influence of social media marketing and electronic word of mouth on purchasing decisions.